Florida 4-H Shotgun Record Book: 4H-SSR-10/4H378, 11/2017 - Dillard, Julie P.; Culen, Gerald (EDIS, 2018)
This 11-page project book discusses goals of the National 4-H Shooting Sports Program and allows 4-H members to record goals and objectives for the year, 4-H Shooting Sports activities, learning experiences, community service, service, learning, and leadership, equipment inventory, finances related to their projects, practice sessions, competitions, and placings in order to help them document their growth, development, and progress. Written by Julie P. Dillard and Gerald Culen, and published by the UF/IFAS 4-H Youth Development Department, November 2017. http://edis.ifas.ufl.edu/4h378